Boom Clay pore-water geochemistry at the Mol site: Chemical equilibrium constraints on the concentrations of major elements. (January 2023) - Wang, Lian; Honty, Miroslav; De Craen, Mieke; Frederickx, Lander
Abstract: It is important to understand the mechanisms controlling the chemistry of the pore water in the Boom Clay, which has been studied as a reference host rock for the geological disposal of radioactive waste. The chemistry of the pore water and the related properties of the Boom Clay were investigated experimentally. This paper presents the results of equilibrium calculations and discusses the probable chemical constraints that control the concentrations of major elements in the pore water. The present-day Boom Clay pore water is a dilute NaHCO3 solution of 10–20 mM, and the concentration increases with the depth of the Boom Clay over a thickness of 65 m around the underground laboratory at approximately 200 m below sea level. The present-day NaHCO3 water is likely a result of freshwater infiltration, and the concentration profile observed must have been affected by waters from upper and lower aquifers. Among the minerals found in the Boom Clay, equilibrium calculations indicate that the pore water is in equilibrium with calcite, dolomite, siderite, pyrite, and quartz. Aluminium silicate minerals, kaolinite and chlorite, are also possibly in equilibrium, but their saturation states cannot be fully demonstrated mainly because of uncertainties associated with the pore-water concentration of aluminium. Cation exchange, an important property of clays, seems to be controlling only the pore-water concentration of potassium. Concentrations of other cation exchangeable elements, such as calcium and magnesium, are more likely regulated by the solubility of carbonate minerals. On clay surfaces, however, cation-exchange reactions are evidenced and control occupancies of all exchangeable cations. The cation-exchange pool on clay responds to the increase in NaHCO3 concentration with depth, and the surface occupancies vary according to the selectivity of exchangeable cations. Equilibrium calculations allow us to propose a Boom Clay reference model that is able to explain the observed pore-water chemistry. This model is compared to other models in the literature, such as those for the Opalinus Clay in Switzerland and Callovo-Oxfordian Clay in France, which have also been studied for the purpose of radioactive waste disposal. Future studies to improve our understanding of the Boom Clay pore-water geochemistry include i) accurate determination of the pore-water concentration of aluminium, which is crucial for studying the mineral saturation state of aluminium silicates; ii) improving understanding of the mineralogical composition of dolomite in the Boom Clay and its dissolution mechanisms; iii) reassessment of magnesium cation-exchange occupancy on clay surfaces; and iv) improving pore-water sampling and analysis techniques with respect to pH and pCO2 measurements to avoid perturbations to water samples so that the in situ conditions can be preserved to a maximum extent. Highlights: Pore-water model of the Boom Clay at the Mol site, Belgium. Model validated by water and clay cation exchange data stratigraphically. Model with 7 minerals buffering the pore-water composition. Model applicable to other clays.